Re-thinking River Diversion Projects- A Political Ecology Perspective - Singh, Neha; Mishra, Neeraj; Murugesan, Vignesh (International Journal of Engineering and Technology, 2018)
The usage of pipelines to make water available to people has been widely discussed phenomenon throughout the world. Less argued are the projects which divert tributaries from larger rivers via small diversion channels for the sake of short-term goals that work around natural waterscape. River Khan is one such smaller stream which accumulates the entire waste of Indore city and has been diverted from its larger stream River Kshipra in the wake of KumbhMela 2016, to keep the larger stream clean. In this context, the paper investigates the discrepancies of this project and identifies the political and economic forces involved in the formation of such projects during events like KumbhMela. Using the theory of political ecology, the paper attempts to understand the complexities surrounding environment and development. Through government policies and influence of material conditions on culture, the paper also explores the unfair relations amid societies that influence the natural environment.Â